PENINGKATAN PENGETAHUAN TELEFARMASI SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN MASYARAKAT DALAM KELOLA OBAT RUMAH TANGGA - Octavia, Devi Ristian; Rohmah, Nanda Adeliyatur; Putri, Dwita Julia; Fifianti, Enggar Ayu; Husain, Habib (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Managing medicines in the household is one of the important points for maintaining public health. The use of drugs must always fulfill the rationality aspect of treatment so that people get the positive benefits of drugs. Rational use of drugs can be done if the public has good knowledge. Alternative telepharmacy is expanding the reach of pharmacies, with the existence of an online media-based health information system. This community service activity aims to describe the results of community service activities which aim to increase public knowledge about telepharmacy as an effort to manage medicine at home properly and correctly. Community service is carried out by providing direct education through the focus group discussion (FGD) method with educational media in the form of leaflets to 21 posyandu cadres. The success of community service activities is evaluated by providing a pretest and posttest. The results of the activity survey show that the difference in partner scores before being given education was 33.3% and after being given education, namely 88.8%, and the community's satisfaction with this service activity. These results show an increase in public knowledge about telepharmacy after the disclosure of the material. Community service activities through providing education can increase public knowledge about the importance of telepharmacy services as community assistance in managing medicines well in the household.